Mediated Intercultural Communication Barrier in No Drama Zone! group - Lizal, Valentino (Jurnal e-Komunikasi, 2015)
This research study aimed to describe the mediated intercultural communication barriers in the No Drama Zone! group. This study is a qualitative descriptive type of research, with case study method. By doing in depth interview and observation, researcher found two barriers that generates other barriers in the group’s mediated intercultural communication. The two big barriers were: language and physical barriers. Language barriers in this group generated two barriers, emotional barrier and perception barrier. While the physical barrier generated two barriers, the time barrier and environment barrier. Each barrier had relation with the differences of cultural backgrounds and the computer mediated communication. This research study can be used as foundation for research regarding the mediated intercultural communication with PS4 as one of the tools.